1999
DOI: 10.1161/01.res.84.6.655
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide and C-Type Atrial Natriuretic Peptide Stimulate Primary Aortic Smooth Muscle Cell Migration via a cGMP-Dependent Mechanism

Abstract: Abstract-Migration of aortic smooth muscle cells is thought to be of essential importance in vascular restenosis, remodeling, and angiogenesis. Recent studies have shown that NO donors inhibit the migration of subcultured aortic smooth muscle cells. However, there is evidence that NO elicits opposite effects on cell proliferation in primary versus subcultured cells, indicating fundamental differences among different models of aortic smooth muscle cell cultures. The purpose of the current study was to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 55 publications
4
80
0
Order By: Relevance
“…12 We did not use ODQ with noninduced cells because insulin did not affect cGMP production or migration in those cells, and it has been reported that ODQ per se does not affect VSMC migration. 17 These data indicate that the inhibition by insulin of the migration of induced VSMCs is dependent on the stimulation by the hormone of cGMP production. The findings that, in the absence of insulin, cells with iNOS have increased basal cGMP levels and lower migration rates compared with noninduced cells indicate that basal cGMP production induced by iNOS-derived NO inhibited the migration of these VSMCs.…”
Section: Discussionmentioning
confidence: 84%
“…12 We did not use ODQ with noninduced cells because insulin did not affect cGMP production or migration in those cells, and it has been reported that ODQ per se does not affect VSMC migration. 17 These data indicate that the inhibition by insulin of the migration of induced VSMCs is dependent on the stimulation by the hormone of cGMP production. The findings that, in the absence of insulin, cells with iNOS have increased basal cGMP levels and lower migration rates compared with noninduced cells indicate that basal cGMP production induced by iNOS-derived NO inhibited the migration of these VSMCs.…”
Section: Discussionmentioning
confidence: 84%
“…25,39 This difference appears to be correlated with the different cytoskeletal phenotypes of the 2 cell types, inasmuch as cells isolated from newborn rats express a phenotype less differentiated than that of cells isolated from adult rats. 15 Moreover, the motility stimulatory effect of NO appears to require another nonmembrane protein tyrosine phosphatase, SHP2, 39 as opposed to the present results, which implicate PTP1B as an inhibitor of cell motility.…”
Section: July 2002mentioning
confidence: 99%
“…Thus, the improved wound healing by this compound was likely a result of cells migrating into the wounded area. Other studies have also shown that NO increases cell migration, but it can also inhibit motility, depending on the type of cell, level and duration of NO exposure, and assay conditions [44][45][46][47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 97%